1994
DOI: 10.1037/0097-7403.20.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Second-order conditioning and Pavlovian conditioned inhibition: Operational similarities and differences.

Abstract: Procedures for establishing second-order excitation (conditioned stimulus [CS] 1-unconditioned stimulus [US] trials followed by CS2-CS1 trials) are highly similar to those for Pavlovian conditioned inhibition (CS1-US trials interspersed with CS2-CS1 trials). Conditioned suppression in rats was used to identify the critical operational differences that result in second-order excitation as opposed to Pavlovian inhibition. No, few, or many CS2-CS1 trials were either interspersed with or given after CS1-US trials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 20 publications
7
98
1
1
Order By: Relevance
“…When CS X is later presented in compound with a transfer excitor B within a summation test, the BX compound evokes weaker responding than when B is presented alone. Yin, Barnet, and Miller (1994) found that with few AXϪ trials, CS X came to act as a second-order excitor. However, with more AXϪ trials, while holding the number of A 3 US trials constant, CS X came to act as a conditioned inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…When CS X is later presented in compound with a transfer excitor B within a summation test, the BX compound evokes weaker responding than when B is presented alone. Yin, Barnet, and Miller (1994) found that with few AXϪ trials, CS X came to act as a second-order excitor. However, with more AXϪ trials, while holding the number of A 3 US trials constant, CS X came to act as a conditioned inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment can result in CS X eliciting either excitatory responding (i.e., second-order conditioning) or behavior indicative of inhibition (i.e., Pavlovian conditioned inhibition). Interestingly, some studies found that second-order conditioning occurs after few AX noUS trials, followed by the development of Pavlovian conditioned inhibition after many AX noUS trials (Stout, Escobar, & Miller, 2004;Yin, Barnet, & Miller, 1994). These authors (also see Gewirtz & Davis, 2000) interpreted these results as indicative of the operation of two processes that develop at different rates.…”
mentioning
confidence: 91%
“…The first simulation regards the aforementioned transition from second-order conditioning (e.g., Pavlov, 1927;Rizley & Rescorla, 1972) to Pavlovian conditioned inhibition (e.g., Pavlov, 1927) as a function of the number of trials (Stout et al, 2004;Yin et al, 1994). Figure 1 summarizes the design of the simulation (see table in the inset).…”
Section: Some Contrary Associative Effects Explained By the Response mentioning
confidence: 99%
See 1 more Smart Citation
“…Yin, Barnet, & Miller, 1994). Analogously, theories of causal learning may regard the lever as a cause of a cause, or as a causal preventer.…”
Section: Predictions Of Substantive Views Of Causal Cognitionmentioning
confidence: 99%